2020
DOI: 10.15446/av.enferm.v38n2.83297
|View full text |Cite
|
Sign up to set email alerts
|

Perfil dos atendimentos oncológicos de uma macrorregião de saúde brasileira

Abstract: Objetivo: conhecer a configuração epidemiológica dos atendimentos oncológicos em uma macrorregião de saúde brasileira, localizada no estado de Minas Gerais, entre 2008 e 2017.Materiais e métodos: estudo quantitativo, exploratório, transversal e descritivo, realizado com dados secundários de cinco municípios localizados no estado de Minas Gerais.Resultados: houve 54.206 atendimentos a indivíduos com câncer, com predominância do sexo masculino (53,38 %), faixa etária de 60 a 79 anos (49,95 %), cor branca (79,08 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
0
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
1
0
0
4
Order By: Relevance
“…Given this scenario, it can be inferred that these patients are more exposed to socioeconomic conditions that trigger neoplastic pathogenesis, such as smoking, alcohol consumption, dietary habits, and obesity (ASSUNÇÃO and FRANÇA, 2020;MALTA et al, 2020). These findings were consistent with the results of a quantitative, cross-sectional, exploratory, and descriptive study in five major municipalities in the southern health macro-region of the state of Minas Gerais, encompassing 54,206 appointments from 2008 to 2017, which showed a predominance of the age group between 60 and 79 years (49.95%) (PAIVA et al, 2020). Similarly, the findings were in line with a study conducted in a population residing in the state of Pará, between 2013 and 2020, which https://www.nucleodoconhecimento.com.br 215 RC: 150096 Available in: https://www.nucleodoconhecimento.com.br/health/complexity-oncology found that the most affected by breast cancer were women aged 45 to 54 years (30.20%) (NEVES et al, 2021).…”
Section: Discussionsupporting
confidence: 85%
“…Given this scenario, it can be inferred that these patients are more exposed to socioeconomic conditions that trigger neoplastic pathogenesis, such as smoking, alcohol consumption, dietary habits, and obesity (ASSUNÇÃO and FRANÇA, 2020;MALTA et al, 2020). These findings were consistent with the results of a quantitative, cross-sectional, exploratory, and descriptive study in five major municipalities in the southern health macro-region of the state of Minas Gerais, encompassing 54,206 appointments from 2008 to 2017, which showed a predominance of the age group between 60 and 79 years (49.95%) (PAIVA et al, 2020). Similarly, the findings were in line with a study conducted in a population residing in the state of Pará, between 2013 and 2020, which https://www.nucleodoconhecimento.com.br 215 RC: 150096 Available in: https://www.nucleodoconhecimento.com.br/health/complexity-oncology found that the most affected by breast cancer were women aged 45 to 54 years (30.20%) (NEVES et al, 2021).…”
Section: Discussionsupporting
confidence: 85%
“…Esses achados foram consistentes com os resultados de um estudo quantitativo, transversal, exploratório e descritivo de cinco municípios-polo da macrorregião de saúde sul do estado de Minas Gerais em que contemplou 54.206 atendimentos no período de 2008 a 2017 evidenciando predominância do grupo etário entre 60 e 79 anos (49,95 %) (PAIVA et al, 2020). De modo semelhante, os achados foram condizentes com os encontrados em estudo realizado em uma população residente no estado do Pará, entre 2013 e 2020, que observou que entre as mais acometidas pela neoplasia mamária foram mulheres que estavam entre 45 e 54 anos de idade (30,20%) (NEVES et al, 2021).…”
Section: Discussionunclassified
“…Estos hallazgos son consistentes con los resultados de un estudio cuantitativo, transversal, exploratorio y descriptivo en cinco municipios polo de la macrorregión de salud del sur del estado de Minas Gerais, que abarcó 54,206 atenciones en el período de 2008 a 2017 y mostró una predominancia del grupo de edad entre 60 y 79 años (49,95%) (PAIVA et al, 2020). De manera similar, estos hallazgos son coherentes con los encontrados en un estudio realizado en una población residente en el estado de Pará, entre 2013 y 2020, que observó que las mujeres más afectadas por el cáncer de mama tenían entre 45 y 54 años de edad (30,20%) (NEVES et al, 2021).…”
Section: Discussionunclassified